PENGEMBANGAN LUDO WORD GAME SEBAGAI MEDIA PEMBELAJARAN PADA MATERI MINYAK BUMI KELAS XI SMA - Iswendi, Sakinah, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The purpose of this research was to produce Ludo Word Game (LWG) chemistryas a learning media in petroleum material of high school class XI was valid andpractical. The type of research was Research and Development (R&D) which used 4-Dmodels. This study examined the level of validity and practicality of the product. Datacollecting was done by validity and practicality questionnaires. Data analyzed by theCohen Kappa formula. Chemical LWG was validated by three Chemistry lecturers atFMIPA UNP and two chemistry teachers from SMAN 1 Gunung Talang. Thedetermination of the practicality level was carried out by two chemistry teachers atSMAN 1 Gunung Talang and 32 students in class XI MIPA 1 of SMAN 1 GunungTalang. From the data analysis, it was found that the chemical LWG as a media oflearning in petroleum material had a validity of 0.84 with a very high validity categoryand the practicality value of the teacher was 0.89 and the students were 0.92 with avery high practicality category. This data shows that the chemical LWG as a media oflearning was developed can be used for petroleum material in class XI SMA.Keywords: Chemical LWG, learning media, petroleum, research and development, 4-Dmodel.